What is the association of lipid levels and incident stroke?. (1st October 2016) - Glasser, Stephen P.; Mosher, Aleena; Howard, George; Banach, Maciej
Abstract: Background: The association between lipid levels and stroke rates is less than lipid levels and coronary heart disease (CHD). Objective. To assess if there are geographic, racial, and ethnic differences in total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C) and triglyceride levels with incident stroke. Methods: From theRE asons forG eographicA ndR acialD ifferences inS troke (REGARDS) study we evaluated baseline levels of LDL-C, HCL-C, TC, Non-HDL-C (Total-HDL-C) and triglycerides in participants free of prevalent stroke at baseline. Cox Proportional-Hazard models were the main analytical tool used to examine the association between incident stroke and lipids. For each adjusted lipid measure (LDL-C, HDL-C, triglycerides, TC, and non-HDL-C) we calculated a series of incremental models. Results: The analysis cohort was 23, 867 participants with a mean follow-up time of 7.5 ± 2.9 years, and 1031 centrally adjudicated strokes (874 ischemic and 77 hemorrhagic strokes). HDL-C baseline level was associated with an overall unadjusted 13% risk reduction (HR 0.87, 95% confidence interval [CI]: 0.81–0.93; p < 0.05; 14% for ischemic and 16% for hemorrhagic strokes), and TC with an 8% (HR 0.92, 95%CI: 0.87–0.99; p < 0.05) risk reduction of all strokes. When the results were fully adjusted a significant association was observed only for LDL-C and non-HDL-C and ischemic stroke. There were no significant differences in these associations when adjusted for age, race, age ∗ race, gender, education, region, or income. Conclusion: In a disease free population, LDL-C and non-HDL-C baseline levels are significantly associated with the risk of ischemic stroke.